2020
DOI: 10.1111/ddi.13041
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the effectiveness of a large multi‐use MPA in protecting Key Biodiversity Areas for marine predators

Abstract: Aim: Marine protected areas can serve to regulate harvesting and conserve biodiversity. Within large multi-use MPAs, it is often unclear to what degree critical sites of biodiversity are afforded protection against commercial activities. Addressing this issue is a prerequisite if we are to appropriately assess sites against conservation targets.We evaluated whether the management regime of a large MPA conserved sites (Key Biodiversity Areas, KBAs) supporting the global persistence of top marine predators.Locat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 59 publications
0
41
0
Order By: Relevance
“…The closure of the krill fishery during summer is an important management measure for reducing spatiotemporal overlap with migratory predator species that disperse away from the maritime zone during winter (GSGSSI, 2013; Handley et al., 2020; Ratcliffe et al., 2015). However, our study confirmed previous observations that gentoo penguins remain in the shelf waters that adjoin their breeding localities throughout the winter (Clausen & Putz, 2003; Hinke et al., 2017; Tanton et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The closure of the krill fishery during summer is an important management measure for reducing spatiotemporal overlap with migratory predator species that disperse away from the maritime zone during winter (GSGSSI, 2013; Handley et al., 2020; Ratcliffe et al., 2015). However, our study confirmed previous observations that gentoo penguins remain in the shelf waters that adjoin their breeding localities throughout the winter (Clausen & Putz, 2003; Hinke et al., 2017; Tanton et al., 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In 2001, 96% and 100% of gentoo penguin locations were within 10 and 17 km of shore, respectively (Tanton et al., 2004), which led to the conclusion that NTZ1 would prevent overlaps of their foraging distribution with the krill fishery during winter (Handley et al., 2020). Williams et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations